(untitled) (Strojniški vestnik – Journal of Mechanical Engineering, 2017)
This study investigates flow characteristics within centrifugal compressors using computational fluid dynamics. Pressure distribution, flow separation, and efficiency were evaluated under different operating conditions. The optimized impeller geometry significantly enhances compressor performance.